2008
DOI: 10.1177/0886260508314693
|View full text |Cite
|
Sign up to set email alerts
|

Changing Policy and Practice in the Child Welfare System Through Collaborative Efforts to Identify and Respond Effectively to Family Violence

Abstract: The Greenbook provides a roadmap for child welfare agencies to collaborate and provide effective responses to families who are experiencing co-occurring child maltreatment and domestic violence. A multisite developmental evaluation was conducted of six demonstration sites that received federal funding to implement Greenbook recommendations for child welfare agencies. Surveys of child welfare caseworkers show significant changes in several areas of agency policy and practice, including regular domestic violence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 16 publications
(24 reference statements)
1
23
0
1
Order By: Relevance
“…It assessed participants' perceptions on: their IPV and CM Knowledge; Perceptions regarding IPV; Battered Parents; IPV and Reporting CM; Knowledge and Abilities Regarding IPV and CM; Effective Advocacy and Intervention; Training Received; and Workplace Policies. Many of its items were adapted from published instruments on actions taken in response to IPV and CM (e.g., Banks, Landsverk, and Wang 2008;Malik et al 2008;Mills and Yoshihama 2002;Saunders et al 1987;Steen 2009). Others were developed by the researchers to also assess providers' knowledge, perceptions, and beliefs about CM and IPV -the study's main focus, and for which no measures were identified within the peer-reviewed literature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It assessed participants' perceptions on: their IPV and CM Knowledge; Perceptions regarding IPV; Battered Parents; IPV and Reporting CM; Knowledge and Abilities Regarding IPV and CM; Effective Advocacy and Intervention; Training Received; and Workplace Policies. Many of its items were adapted from published instruments on actions taken in response to IPV and CM (e.g., Banks, Landsverk, and Wang 2008;Malik et al 2008;Mills and Yoshihama 2002;Saunders et al 1987;Steen 2009). Others were developed by the researchers to also assess providers' knowledge, perceptions, and beliefs about CM and IPV -the study's main focus, and for which no measures were identified within the peer-reviewed literature.…”
Section: Methodsmentioning
confidence: 99%
“…Research shows that intimate partner violence (IPV) places children at risk for maltreatment (Banks, Landsverk, and Wang 2008;Steen 2009). Child abuse is estimated to be present in about 40 % of IPV cases (e.g., Herrenkohl et al 2008).…”
mentioning
confidence: 98%
“…Banks et al, 2008; . Goddard and Hiller (1993) examined records for over 200 children presenting at the child protection unit of a metropolitan Australian hospital.…”
Section: Overlaps Between Intimate Partner Violence and Child Abusementioning
confidence: 95%
“…Since child protection services have not historically been concerned for the safety of women (Banks, Landsverk, & Wang, 2008;Zannettinno, 2006), it is understandable that domestic violence organisations sometimes have serious concerns about sharing confidential information. They are worried about the risk that information may be passed on to the perpetrator, thus threatening the safety of the mother and child.…”
Section: Trustmentioning
confidence: 99%